2015
DOI: 10.4236/ojped.2015.52027
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Graves’ Disease and Cholestatic Jaundice: Case Series and Review of the Literature

Abstract: Cholestatic jaundice and elevated liver enzymes are uncommon, but recognized, manifestations of neonatal thyrotoxicosis. Current guidelines for evaluation of cholestatic jaundice and reviews in Neonatology literature do not discuss hyperthyroidism in the differential diagnosis of cholestatic jaundice. We report two cases of neonatal thyrotoxicosis secondary to neonatal Graves' disease that presented with cholestatic jaundice and elevated liver enzymes at birth. Early recognition of thyrotoxicosis as a cause of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Additional causes for the liver dysfunction in these patients may include concomitant autoimmune liver disease, drug‐induced dysfunction from antithyroid medication, and/or sepsis 49 . In the pediatric population, there are a few case reports of cholestasis and/or liver failure presenting as neonatal hyperthyroidism due to maternal Graves’ disease 50–56 . Among elder pediatric patients there are only two case reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional causes for the liver dysfunction in these patients may include concomitant autoimmune liver disease, drug‐induced dysfunction from antithyroid medication, and/or sepsis 49 . In the pediatric population, there are a few case reports of cholestasis and/or liver failure presenting as neonatal hyperthyroidism due to maternal Graves’ disease 50–56 . Among elder pediatric patients there are only two case reports.…”
Section: Discussionmentioning
confidence: 99%
“…Although hyperthyroidism causing hepatitis is well documented, we believe that the case we describe here demonstrates coincidental presentation of hepatitis and thyroiditis, with the biochemical thyroid picture altered by sick euthyroid syndrome secondary to the hepatitis. The most likely explanation for the biochemical hyperthyroidism was a transient form of thyroiditis, indicated mainly by reduced I‐123 uptake on the thyroid scan, a characteristic finding for all forms of thyroiditis 55 . Although an undiagnosed infectious etiology of the subacute form of thyroiditis was considered, the eventual identification of positive thyroid peroxidase antibodies suggested that autoimmune Hashimoto's thyroiditis was the likely etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Their mothers had previous histories of thyrotoxicosis and were treated with radioactive iodine; both mothers became hypothyroid and were placed on thyroxine replacement therapy. The thyroid profiles of the babies showed evidence of GD and both were started on carbimazole therapy; this led to a gradual improvement of manifestations [6] The exact mechanism for cholestasis is not fully understood. T3 plays a role in bilirubin metabolism and increased levels are thought to cause the accumulation of bilirubin precursors.…”
Section: Discussionmentioning
confidence: 99%
“…Raghu U Varier et al [7] reported a infant born prematurely at 35.5weeks of gestation and presented with irritability, mild exophthalmos, tachypnea and jaundice but did not have other clinical manifestations of neonatal Graves' disease. O. Almadhoun et al [8] reported 2 cases of neonatal hypothyroidism presented with cholestatic jaundice. Both of them are preterm infants delivered to mothers with hypothyroidism on hormone replacement therapy.…”
Section: Discussionmentioning
confidence: 99%